Effects of rapamycin pretreatment on blood-brain barrier disruption in cerebral ischemia-reperfusion. (4th May 2016) - Chi, Oak Z.; Mellender, Scott J.; Barsoum, Sylviana; Liu, Xia; Damito, Stacey; Weiss, Harvey R.
Abstract: The mammalian target of rapamycin (mTOR) pathway is essential in neuronal survival and repair in cerebral ischemia. Decreases in blood-brain barrier (BBB) disruption are associated with a decrease in neuronal damage in cerebral ischemia. This study was performed to investigate how pre-inhibition of the mTOR pathway with rapamycin would affect BBB disruption and the size of the infarcted cortical area in the early stage of focal cerebral ischemia-reperfusion using quantitative analysis of BBB disruption. Rats were treated with 20 mg/kg of rapamycin i.p. once a day for 2 days (Rapamycin Group) or vehicle (Control Group) before transient middle cerebral artery (MCA) occlusion. After one hour of MCA occlusion and two hours of reperfusion, the transfer coefficient (Ki ) of 14 C-α-aminoisobutyric acid ( 14 C-AIB) to measure the degree of BBB disruption and the size of the cortical infarct were determined. Ischemia-reperfusion increased the Ki in the Rapamycin treated (+15%) as well as in the untreated control group (+13%). However, rapamycin pretreatment moderately decreased Ki in the contralateral (−30%) as well as in the ischemic-reperfused (−29%) cortex when compared with the untreated control group. Rapamycin pretreatment substantially increased the percentage of cortical infarct compared with the control group (+56%). Our data suggest that activation of mTOR pathway is necessary for neuronal survival in the early stage of cerebral ischemia-perfusion and that the reason for the enlarged cortical infarct by rapamycin pretreatment may be related to its non-BBB effects on the mTOR pathway.